Spatial Analysis of Rural Settlement Systems within the Framework of Land Use Planning Using Geographic Information Systems (Case Study: Aq Su Rural District) - Seyed Mohammad Mousavi Parsaei (اکولوژی انسانی, 2023)
Land use planning encompasses the rational organization of economic, social, cultural, and environmental development aspects. Spatial organization of settlement systems within the framework of land use planning is closely related to the spatial-physical patterns of rural settlements. Achieving a balanced development in rural areas depends on finding suitable spatial patterns in settlement systems generally and rural settlements specifically. Analyzing rural settlements in terms of economic, social, and environmental aspects without considering ecological, spatial, and vulnerability approaches is ineffective. Rural settlements face challenges such as poverty, income inequality, rural migration, village abandonment, neglect of spatial-physical management, and high vulnerability. Factors such as altitude, slope, geological structure, faults, water resources, soil, vegetation, and land use serve as natural bases that significantly influence the identification of suitable and unsuitable areas for rural settlement risk assessment.This applied-developmental study employs library and survey methods to evaluate the ecological and environmental capabilities of the Aq Su region in Kalaleh County for organizing settlement systems. To measure the impact of vulnerability factors on the spatial distribution of rural settlements, multiple regression analysis was utilized. Subsequently, spatial database preparation in a GIS environment (ArcGIS) was performed. After standardizing the criteria using fuzzy logic and AHP methods, weights were assigned to each criterion in the software environment. By integrating these criteria based on the AHP model and fuzzy logic, a final map indicating suitable and unsuitable areas was generated. The study area in the resulting map was classified into highly suitable, suitable, and unsuitable categories for planning various settlement activities.